Komunikasi Injil dalam Konteks Moderasi Beragama di Indonesia - Juanda Manullang (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2023)
Communicating the Gospel in the context of religious moderation in Indonesia has its own challenges and obstacles. Therefore, we need the right strategy so as not to cause conflict between religions. This article discusses moderate communication strategies in the context of religious diversity in Indonesia so that the message of the Bible can be conveyed effectively. The literature study method was used for writing this article and the results obtained were that the gospel communication strategy in the context of religious moderation in Indonesia can be carried out using language that is easy to understand, building good relationships with people of other religions, using social media, and promoting universal values ​​and avoiding fanaticism and extremism.